Organized crime and criminal careers - Kleemans, Edward R. (Crime and justice, 2020)
Widely accepted findings in developmental and life-course criminology cannot be extended to criminal careers of organized crime offenders. While most offenders begin offending at a young age, criminal careers in organized crime are generally characterized by a late onset typically characterized by relatively serious offending. Different patterns exist for different groups, including early starters, adult-onset offenders, and offenders with no previous judicial contacts, but all studies find a significant share of adult-onset offenders. Social relationships, including family, friendship, and work ties, are importantly related to becoming involved in organized crime. Involvement mechanisms are diverse; both conventional and criminal capital are important. Children of organized crime offenders have a high risk of intergenerational continuity of crime. Factors that promote desistance for most offenders, such as employment, sometimes have different meanings for organized crime participants, as some occupations provide criminal opportunities and some work settings foster offender convergence. Widely used concepts such as specialization and desistance are less applicable because of the distinctive nature of organized crime offenses and careers. The most urgent issue for future research is to incorporate the roles of co-offenders into analyses of individual criminal careers.